PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIVE KARTEN DENGAN AUGMENTED REALITY UNTUK KETERAMPILAN MENULIS BAHASA JERMAN KELAS XI SMA - Safitri, Aura; Wahyuningsih, Fahmi (LATERNE, 2025)
Interactive Karten Media with Augmented Reality is a learning media designed in the form of cards and equipped with 3D objects. The background of this study was that students still have difficulty in writing descriptive text (Beschreibung). The formulation of the problem in this study was how the development process and feasibility of Interaktive Karten media with Augmented Reality for German Writing Skills Grade XI SMA. This study aimed to determine the process and feasibility of Interaktive Karten media with Augmented Reality for German Writing Skills Grade XI SMA. This research used the Research and Development (R&D) method with the ADDIE development model, limited to 3 stages: Analysis, Design, Development. The material validation results got a score of 80% with a category worth using with revision. The results of media validation scored 96% with a category worth using without revision. Then, the results of practitioner validation scored 80% with a category worth using with revision. So, it could be concluded that Interaktive Karten media with Augmented Reality is feasible to use as medium for learning German in class XI SMA.